Managing deadlock: organisational development in the British First Army, 1915 - Watt, Emir Patrick James (The University of Edinburgh, 2018)
In terms of the British Army in the Great War, the study of whether or how the army learned has become the dominant historiographical theme in the past thirty years. Previous studies have often viewed learning and institutional change through the lens of the ‘learning curve’, a concept which emphasises that the high command of the British Army learned to win the war through a combination of trial and error in battle planning, and through careful consideration of their collective and individual experiences. This thesis demonstrates that in order to understand the complexities of institutional change in the Great War, we must look beyond ill-defined concepts such as the learning curve and adopt a more rigid framework. This thesis examines institutional change in the British First Army in the 1915 campaign on the western front. It applies concepts more commonly found in business studies, such as organisational culture, knowledge management and organisational memory, to understand how the First Army developed as an institution in 1915. It presents a five-stage model – termed the Organisational Development Model – which demonstrates how the high command of the First Army considered their experiences and changed their operational practices in response. This thesis finds that the ‘war managers’ decision-making was affected by a number of institutional and personal ‘inputs’ which shaped their approach to understanding warfare. This thesis examines the manner in which new knowledge was created and collated in the immediate post-battle period, before studying how the war managers considered new information, disseminated it across the force and institutionalised it in the organisation’s formal practices, structures and routines. In a broad sense, this thesis does three things. First, by examining how the army learned it moves beyond standard narratives of learning in the British Army in the Great War and highlights the complex interplay between personal and institutional learning processes. Second, by focusing on institutional change in the 1915 campaign, it sheds new light on an understudied yet crucial part of the British war experience. Finally, in creating the Organisational Development Model, it provides a robust platform on which future research can be built.
Keywords: First World War; World War I; organisational culture; 1914-1918; learning curve; British Army; 1915 campaign